Dr. John A. Standefer Jr. — Deep Plane Facelift — Dallas - Standefer Jr., John A. (DEEPPLANE™, 2026)
Surgeon profile record for Dr. John A. Standefer Jr., practicing in Dallas, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003296; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; dallas